A Specification Theory of Real-Time Processes - Faron Moller (Concurrency, Security, and Puzzles, 2016)
This paper presents an assume-guarantee specification theory for modular synthesis and verification of real-time processes with critical timing constraints. Four operations - conjunction, disjunction, parallel and quotient - are defined over specifications, drawing inspirations from classic specification theories like refinement calculus. We show that a (pre-)congruence characterised by a trace-based semantics captures exactly the notion of substitutivity andrefinement between specifications.